The Role of Competitiveness in Economic Security - Understanding the Concept in Romanian Economy - MIHĂESCU, Adina (Studia Universitatis Babeș-Bolyai Historia, 2025)
In the era of globalization, the inter-linking of economies and increased competition have made competitiveness a fundamental element for the survival and development of companies in the international marketplace. It manifests itself at several levels, both between countries and between their national economies or within private companies. To make progress, states need to attract investment, increase productivity, exports and jobs, and support entrepreneurship, innovation and technological development. This underlines the importance of an integrated strategy to promote competitiveness across all sectors. Thus, competitiveness, an essential attribute of economic security, depends as much on policy makers and the measures they take as on the management of private sector companies and their ability to adapt and evolve in a globalizing economy. Rezumat: În era globalizării, conexiunile dintre economii și creșterea competiției au făcut din competitivitate un element un element fundamental pentru supraviețuirea și dezvoltarea companiilor pe piața internațională. Aceasta se manifestă pe mai multe niveluri, atât între state, cât și între economiile lor naționale sau în cadrul companiilor private. Pentru a progresa, statele trebuie să atragă investiții, să crească productivitatea, exporturile și locurile de muncă, și să susțină antreprenoriatul, inovația și dezvoltarea tehnologică. Această situație subliniază importanța unei strategii integrate pentru a promova competitivitatea în toate sectoarele. Astfel, competitivitatea, un atribut esențial al securității economice, depinde atât de decidenții politici și măsurile luate de aceștia, cât și de managementul companiilor din sectorul privat și abilitățile acestora de a se adapta și a evolua în contextul globalizării economiei. Cuvinte-cheie: securitate economică, securitate națională, competitivitate